NOSE TO BRAIN DELIVERY OF FROVATRIPTAN LOADED IN PLGA NANOPARTICLES: A PROMISING APPROACH FOR MIGRAINE THERAPY - AJEET KUMAR; SARAVANAN K; SAURABH SHARMA (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: The objective of the research was to formulate and evaluate frovatriptan succinate (FS)-loaded poly (lactic-co-glycolic acid) (PLGA) nanoparticles (NP) for migraine therapy to improve its therapeutic effect and reduce dosing frequency. Methods: The objective of the present study was to develop FS-loaded NP for brain targeting to improve bioavailability, decrease dose and frequency of dosing, reduce side effects, and improve therapeutic efficacy. A 32 factorial design was employed to formulate a nanoparticulate drug delivery system using PLGA. PLGA NP were prepared by the nanoprecipitation technique and characterized for particle size, zeta potential, surface morphology, entrapment efficiency (EE), and in vitro drug release. Results: The particle size of the optimized formulation NPopt was found to be 236.1 nm±0.21 nm with EE 63.82±0.643%. Zeta potential was found to be −30.3 mV. Transmission electron microscopy studies indicated that the NPs were spherical with smooth surface. NPopt gave 84.15±1.308% sustained release in phosphate buffered saline pH 6.4 after 24 h, following Quasi-Fickian diffusion-based release mechanism. Stability study showed that the formulation NPopt was more stable at 5±1°C than room temperature. These results showed that FS-loaded PLGA NP can be a potential carrier for brain targeting. Conclusion: The results suggest that FS-loaded PLGA NP can be a potential carrier for brain targeting with promising therapeutic action.